2021
DOI: 10.1017/s1368980021001245
|View full text |Cite
|
Sign up to set email alerts
|

Restaurant kids’ meal beverage offerings before and after implementation of healthy default beverage policy statewide in California compared with citywide in Wilmington, Delaware

Abstract: Objective: In 2019, California and Wilmington, Delaware implemented policies requiring healthier default beverages with restaurant kids’ meals. This study assessed restaurant beverage offerings and manager perceptions. Design: Pre-post menu observations were conducted in California and Wilmington. Observations of cashiers/servers during orders were conducted pre-post implementation in California and post-implementation in Wilmington. Changes in California were compared using multilevel l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 14 publications
(22 reference statements)
0
10
1
Order By: Relevance
“…Prior work examining California QSR beverage offerings with children's meals before and after implementation of SB1192 demonstrated that the number of in-restaurant and drive-through QSR menus including only law-consistent beverages significantly increased nearly sixfold, from 10 % to 66 % (34) . However, 1-year post SB1192 implementation, one-third of sampled QSR were still not consistent with the law in regard to the menu board and only 1 % were offering beverages during in-person ordering in a manner consistent with the legislation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior work examining California QSR beverage offerings with children's meals before and after implementation of SB1192 demonstrated that the number of in-restaurant and drive-through QSR menus including only law-consistent beverages significantly increased nearly sixfold, from 10 % to 66 % (34) . However, 1-year post SB1192 implementation, one-third of sampled QSR were still not consistent with the law in regard to the menu board and only 1 % were offering beverages during in-person ordering in a manner consistent with the legislation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the same study found offerings on menus/menu boards did not change after similar legislation was passed in Wilmington, Delaware. This could be because no restaurant managers in Wilmington reported knowing about the law, compared with nearly one-third of California managers; or, it could be because a smaller proportion of Wilmington restaurants were chains and chains might be expected to have increased awareness and more systematic implementation of applicable legislation (34) . Online ordering platforms, however, were not examined and to our knowledge there is no published literature on the implementation of SB1192 or similar legislation on online ordering platforms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in line with other studies that tried to help restaurateurs better adapt their menus to the Mediterranean diet or healthier diets by giving personalized directions to restaurateurs regarding the dishes listed on their menus. Such instructions included introducing more side vegetables, offering fruit for dessert, and using extra virgin olive oil for different types of cooking (20,(28)(29)(30). Additionally, the pandemic resulted in some changes to customer preferences, and restaurateurs could be interested in acting on those changes, such as by offering more vegetarian/vegan or allergen-free dish choices.…”
Section: Discussionmentioning
confidence: 99%
“…A pre-post study of healthy default beverage policies enacted in CA and Wilmington, DE, found that more fast-food restaurants in low-income communities in CA offered healthy beverages as the default option with kids’ meals on the menu board after a state law came into effect (the percentage of restaurants offering healthier beverages complying with the state law increased from 9.7% at baseline to 66.1% after the policy came into effect). There was no change, however, in the proportion of restaurants offering healthy beverage options with kids’ meals in Wilmington (30.8% of restaurants offered healthy beverages with kids’ meals on the menu board at both the time points) [ 23 ]. Further, in CA, fewer sales associates offered healthy beverages to customers verbally when a kids’ meal was ordered (the verbal offers decreased from 5.0% at baseline to 1.0% after policy enactment) [ 23 ].…”
Section: Introductionmentioning
confidence: 99%